The therapeutic role of honey for treating acute cough in the pediatric population. A systematic review - Mohamed Qasim Toorani (Hygeia Press di Corridori Marinella, 2019)
An acute cough is a common reason for medical consultation in the pediatric age group, particularly in the setting of an upper respiratory tract infection (URTI). Traditionally, honey is used as a home remedy for treating an URTI in many parts of the world. Its use is supported by the fact that honey has both antimicrobial and wound-healing properties. Due to its inexpensiveness, easy availability and safety (in children above the age of 12 months), the World Health Organization endorsed the use of honey as a demulcent in the symptomatic relief of a cough and sore throat. A literature review of PubMed identified 6 randomized controlled trials that compared honey against over-the-counter (OTC) cough medications, and no treatment, in the pediatric population. It was shown that honey was more efficacious than no treatment and at least as efficacious as OTC cough medications. As OTC cough medications are associated with morbidity and mortality in pediatrics, the potential utilization of honey as an alternative therapeutic option in pediatrics warrants further objective research in the context of clinical practice.